Does an active lifestyle matter? A longitudinal study of physical activity and health-related determinants in older adults - Teraž, Kaja; Pišot, Saša; Šimunic, Boštjan; Pišot, Rado (Frontiers in Public Health, 2022)
Introduction: It is well known that regular physical activity, and thus an active lifestyle, has positive effects on aging and general well-being. However, the question remains whether regular or increased physical activity can improve self-perception of health status and quality of life in older adults. Methods: We conducted a longitudinal study on a group of active older adults between 2013 and 2021. At baseline, i.e., the 1st measurements (baseline) 147 participants were enrolled (mean age 68.3 ± 5.5), after eight years in 2021 (follow up), 52 older adults (mean age 68.4 ± 5.6 years) were measured. For both measurements, participants reported their PA and SB using Global physical activity questionnaire (GPAQ) and different socio-demographic, environmental determinants, and self-perception of overall well-being. Furthermore, we conducted a qualitative study using semi-structured interviews to obtain subjective data on the changes and events that might affect physical abilities and general health over an eight-year period. Results: At follow up, participants reported lower SBs and PA compared to baseline, but still met health enhancing physical activity (HEPA) standards for total self-reported physical activity (> 3000 METmin/week). In addition, they rated their overall health (p < .001), physical fitness (p < .001), psychological well-being (p < .001) and overall quality of life (p < .001) as better. The qualitative data confirmed that the 8-year period involved changes in physical activity. Specifically, physical work (gardening, working in the vineyards, olive groves) continues, walks (in nature) substituted organized physical activities which diminished SB. Conclusion: Despite the increase in prescribed medications (p = .002), participants' perceptions of general health, physical performance, psychological well-being, and overall quality of life were better at follow-up measurements. This can be explained by their continued active lifestyle and subjective assessment of their condition compared to their generation.